Bare metal stent application to prevent limb occlusion in iliac arteries with severe tortuosity during an endovascular aneurysm repair: a cohort study - Zeng, Xiong; Ju, Zhinan; Min, Xixi; Zeng, Xiande; Chen, Wei; Dai, Kanghui; Zhou, Weimin; Qiu, Jiehua (Frontiers in Cardiovascular Medicine, 2024)
BackgroundThe risk of limb graft occlusion (LGO) after endovascular aneurysm repair (EVAR) is increased by severe tortuosity of the iliac artery. A bare metal stent (BMS) may protect LGO, according to the hypothesis of this single-center retrospective analysis.MethodsAll patients undergoing elective EVAR with a bifurcated stent graft between January 2012 and June 2022 were included in this cohort study. Patients demonstrating significant tortuosity at the iliac angle were incorporated into this study and classified into two groups: group A comprised those who received a BMS. In contrast, group B consisted of those who did not receive a BMS. The primary outcomes were the incidence of limb occlusion and technical success during the follow-up period. However, secondary outcomes included perioperative mortality, external iliac angioplasty, and crossed-limb techniques.StatementThis study has been reported as being in line with the STROCSS criteria.ResultA total of 157 patients (mean age = 71.6 ± 8 years) with infrarenal abdominal aortic aneurysms were enrolled. In total, 50 individuals were included in group A, while 107 were in group B. Overall technical success was 100%, and only one (2%) patient from group A and 17 (15%) from group B suffered from limb occlusion during follow-up (p < 0.05). At a mean follow-up imaging duration of 28.7 ± 23.6 months (range 1–124), the estimated primary limb patency at 2 years was 98% for the BMS group and 84% for the non-BMS group (p < 0.05). There were no changes in perioperative mortality or crossed-limb procedures between the BMS and non-BMS groups. Nonetheless, there were disparities in external iliac angioplasty between the two groups during the follow-up period (p < 0.05).ConclusionDeploying a BMS inside the iliac artery to prevent or treat limb occlusion is a safe and effective strategy, with clear prolonged outcomes concerning patency and re-interventions.